2000
DOI: 10.3989/scimar.2000.64s187
|View full text |Cite
|
Sign up to set email alerts
|

Deep-water Hydromedusae from the Lacaze-Duthiers submarine canyon (Banyuls, northwestern Mediterranean) and description of two new genera, <i>Guillea</i> and <i>Parateclaia</i>

Abstract: SUMMARY: Several species of hydromedusae are reported from material collected by sediment traps placed in the LacazeDuthiers submarine canyon, off Banyuls (north-western Mediterranean). Two new taxa Guillea canyonincolae gen. nov. et sp. nov. and Parateclaia euromarge fam. nov., gen. nov. et sp. nov., are described. The existence of highly-specific hydromedusa populations in other Mediterranean canyons which appear to be related via geological history, topography, hydrographic and ecological features peculiar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
4
11
0
Order By: Relevance
“…asteroides , the Mediterranean counterpart of P . polaris [16, 17, 59, 60]. The ecological and oceanographic features that facilitate the concentration of medusan fauna in submarine canyons and subpolar fjords may therefore explain why we observe a relatively higher richness and abundance of benthopelagic medusae in these unique ocean habitats compared to the generic deep sea.…”
Section: Discussionmentioning
confidence: 91%
“…asteroides , the Mediterranean counterpart of P . polaris [16, 17, 59, 60]. The ecological and oceanographic features that facilitate the concentration of medusan fauna in submarine canyons and subpolar fjords may therefore explain why we observe a relatively higher richness and abundance of benthopelagic medusae in these unique ocean habitats compared to the generic deep sea.…”
Section: Discussionmentioning
confidence: 91%
“…Inside the canyon, copepods and non-copepod Crustacea were less abundant during the winter. The hydromedusae Parateclaia euromarge (Bouillon et al, 2000) appeared as the second contributor to the dissimilarity among seasons in BC, being more abundant in summer and absent in winter and autumn. Moreover, the polychaete larvae in BC showed the highest abundance in summer, but were also present in winter with a slightly lower abundance.…”
Section: Swimmersmentioning
confidence: 99%
“…Several studies focusing on swimmers found in sediment traps have been recently carried out in the Mediterranean Sea, mainly within the frame of geological studies. In terms of biodiversity, these studies lead both to the description of new species, genera, and even families, of cnidarians and polychaetes, as well as to the re-description of other species based on the analysis of new morphological features (Gili et al, 1998(Gili et al, , 1999(Gili et al, , 2000Sardá et al, 2009, Sevastou et al, 2012. Others revealed that canyons in the North Western Mediterranean Sea host unique and specific hydromedusa populations (Bouillon et al, 2000;Gili et al, 1999Gili et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earleria antoniae (Foersteria antoniae: Gili et al, 1998;Bouillon et al, 2000) and Earleria araiae (Foersteria araiae: Gili et al, 1999;Bouillon et al, 2000) were reported from canyons in the Mediterranean sea. Earleria purpurea (Foersteria purpurea : Mackie, 1985;Larson et al, 1992) were reported as one of the benthopelagic species present in fjords of British Columbia in the 50-450 m depth strata, and deeper than 200 m depth in Monterey Bay.…”
Section: Earleria Bruunimentioning
confidence: 99%